Budidaya Kepiting Bakau (Scylla Serrata) Teknologi Apartemen Sistem Resirkulasi Desa Cot Lamkuweueh, Kota Banda Aceh - Said Ali Akbar; Dedi Fazriansyah Putra; Ichsan Rusydi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
It is one of the important and potential economic products of Aceh province. Wild crabs have great potential and prospects for aquaculture development. This can be seen from the large number of ponds in Banda Aceh city. Currently, the mangrove crab farming model using a floating cage system is the most popular in Aceh. The problem is that natural conditions cannot be controlled, so water quality changes drastically, making it difficult for farming to achieve success above 80%. Syiah Kuala University Aquaculture Research Program Community Services Group has developed a mangrove crab farming unit with a vertical apartment system equipped with a water circulation system or RAS. The apartment system is designed with 4 floors, each floor has 10 crab boxes. The time it takes for crabs to molt during spawning is 15-20 days with a survival rate of 80-90%. Hopefully this technology transfer to partners will become an educational model for mangrove crab farmers in Cot Lamkuweueh village, Banda Aceh city.